The Influence of Humour on Learners’ Attitude and Mathematics Achievement: A Case of Secondary Schools in Arusha City, Tanzania - Ngussa, Baraka Manjale; Mbuti, Elias Elisha (IJRDO- Journal of Educational Research, 2017)
While there are many factors which can contribute to success or failure in Mathematics achievement, teaching-learning strategy is an important factor which cannot be ignored. This study employed case study design to investigate the influence of humour as an instructional tool on secondary school learners’ attitude and mathematics achievement in Arusha City, Tanzania. A sample of 412 Form Three students participated by filling the questionnaire. Expert judgment ensured that the questionnaire items provided useful information that corresponds to research questions. Reliability test for three variables yielded conbach’s alpha between 0.73 and 0.79 meaning items in the questionnaire were reliable. Quantitative method in terms of descriptive statistics established mean scores while inferential statistics in terms of t-test and Pearson Product moment corelational coefficient tested differences and relationships respectively. The study concludes that the more the use of humour in teaching, the better the attitude and mathematics achievement. Therefore, it is recommended that Mathematics teachers should increase the use of humour while teaching in order to increase learner’s interest in the subject matter and in that way improve performance